1993
DOI: 10.1577/1548-8640(1993)055<0169:eooyet>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of One-Year Exposures to Gas Supersaturation on Lake Trout

Abstract: Lake trout (Salvelinus namaycush) were reared for 1 year in water with one of six levels of incoming differential gas pressure (AP): 4, 17, 33, 43, 58, or 75 mm Hg. Growth and survival offish were evaluated as measures of response to the potential long-term stress of elevated dissolved gases in rearing water. Mortality rates were not different among fish held in supersaturated water up to AP 58 (108% of total gas saturation), but mortality at AP 75 (110% saturation) was significantly higher after day 28. From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…The report discribed by Person-Le Ruyet et al (2002) also demonstrated that no substantial increase in growth of turbot occurred when the turbot were reared for 30 d in O 2 -supersaturated and saturated water. However, in the study by Krise (1993), growth rate reductions were obvious when lake trout were exposed to gas supersaturation for more than 252 d with a gas pressure ΔP=17 mmHg. In addition, sublethal exposures to different concentrations of dissolved gas significantly affected the growth of chinook salmon and steelhead trout (Dawley and Ebel, 1975).…”
Section: Growth Ratementioning
confidence: 80%
“…The report discribed by Person-Le Ruyet et al (2002) also demonstrated that no substantial increase in growth of turbot occurred when the turbot were reared for 30 d in O 2 -supersaturated and saturated water. However, in the study by Krise (1993), growth rate reductions were obvious when lake trout were exposed to gas supersaturation for more than 252 d with a gas pressure ΔP=17 mmHg. In addition, sublethal exposures to different concentrations of dissolved gas significantly affected the growth of chinook salmon and steelhead trout (Dawley and Ebel, 1975).…”
Section: Growth Ratementioning
confidence: 80%
“…The behavior of larvae exposed to DGS suggests that deleterious effects are associated with sublethal exposure to DGS. Sublethal exposure to DGS has been shown to affect several aspects of performance in other fishes, including swimming performance (Schiewe 1974;Dawley and Ebel 1975), growth (Dawley and Ebel 1975;Cornacchia and Colt 1984;Krise 1993), blood chemistry (Newcomb 1974;Dawley and Ebel 1975), thermal tolerance (Ebel et al 1971), lateral line function (Weber and Schiewe 1976), and predation vulnerability (Mesa and Warren 1997). The buoyant effects of the gas bubbles in the buccal cavity may make it difficult for white sturgeon larvae to move to greater water depths and thus use hydrostatic pressure to alleviate the effects of GBT.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the potentially serious effects that may occur in fish exposed to sublethal gas concentrations have received relatively little quantitative attention, despite being cited often as potential causes of fish losses. Studies have shown that sublethal exposure of fish to DGS can adversely affect swimming performance (Schiewe 1974;Dawley and Ebel 1975), blood chemistry (Newcomb 1974;Dawley and Ebel 1975), growth (Dawley and Ebel 1975;Krise 1993), thermal tolerance (Ebel et al 1971), and lateral line function (Weber and Schiewe 1976).…”
Section: Introductionmentioning
confidence: 99%